Another 'Cushing ulcer'. (11th April 2011) - Hoshino, Chisho; Satoh, Noriyuki; Narita, Masashi; Kikuchi, Akio; Inoue, Minoru
Abstract : The authors describe the case of a 39-year-old man who presented to our hospital with easy fatigability and malaise. On physical examination, hypertension was noted without any cushingoid appearance. Laboratory testing revealed normochromic-normocytic anaemia with positive results of occult blood in the stool, hyperglycaemia and hypokalemia. Upper endoscopy revealed active gastric ulcer with Helicobacter pylori infection, likely causing gastrointestinal bleeding. Endocrine examinations showed that both serum adrenocorticotropic hormone and cortisol were elevated with loss of diurnal variation. A diagnosis of Cushing's disease secondary to pituitary adenoma was made as results of brain MRI and blood sampling from inferior petrosal sinus. In a patient with peptic ulcer disease, physician should be alert to the possible endocrine background.